Convenient Yet Neglected: The Role of Grandparent Kinship Carers. (11th October 2018) - Zuchowski, Ines; Gair, Susan; Henderson, Debbie; Thorpe, Ros
Abstract: Grandparents are increasingly involved in the care and protection of grandchildren. The qualitative Australian study reported here explored how contact between grandparents and their grandchildren could be optimised after child-safety concerns. Interviews and focus groups with seventy-seven participants were undertaken in 2016. In total, fifty-one grandparents and aunties in grand parenting roles, twelve parents, six foster-carers and eight child-protection workers participated in this study. Of the fifty-one participants in grandparent roles, twenty were kinship carers. This article specifically reports on emerging findings regarding grandparents as kinship carers. Key findings reveal that many grandparents were willing to step into the carer role and many wanted to stay connected to grandchildren, although, overall, they received little support. Findings identified the stresses and the fragility of the care arrangements and that at times providing kinship care could endanger carers. Overall, findings point to a perceived notion of kinship care implemented as a cost-effective alternative to foster-care that leaves grandparents without the required support and resources. It is recommended here that grandparents receive greater recognition as kinship carers, and that child-protection systems increase family-inclusive practices that provide better support and resources to kinship carers.